Collect your favourite things! We're moving again! - Oliver, Isabel; Oborn, Veronica (Canberra : AGPS Press, 1995)
Discusses families who move house in Australia and those who assist them.
Children.
Keywords: Australian Defence Force -- Relocation -- Juvenile literature; Moving, Household -- Juvenile fiction; Children of military personnel -- Housing -- Juvenile fiction; Military dependents -- Housing -- Juvenile fiction; Moving, household -- Juvenile literature